Brown-McLean syndrome secondary keratoconus - Qi Wan; Li Chen; Ran Wei; Ying-ping Deng; Ke Ma; Jing Tang (BMC Ophthalmology)
Abstract Background Brown-McLean Syndrome is a rare clinical condition typically presenting as localized edema involving a 2–3 mm peripheral area of the cornea, which often has undergone intraocular surgery. Case report We present a unique case of unilateral Brown-McLean Syndrome (BMS) with concurrent keratoconus in an 18-year-old male patient. The individual sought medical attention due to poor vision in the right eye, which had been unnoticed for a month. Notably, there was no history of ocular surgery or trauma, and the patient did not suffer from any systemic diseases. Clinical examination revealed peripheral corneal edema, extending 2–4 mm from the limbus, exclusively affecting the right eye. Corneal topography indicated the presence of keratoconus, which was an incidental finding during the investigation. Conclusions This case underscores the importance of considering BMS in the differential diagnosis of peripheral corneal edema even in the absence of ocular surgery or trauma. The potential relationship between BMS and keratoconus is explored, suggesting that long-term edema and degeneration of the peripheral cornea could alter its biomechanical properties, leading to deformation and keratoconus. Thorough clinical evaluation and long-term follow-up are crucial in managing such patients.